Enterobacteria 2022
DOI: 10.5772/intechopen.102618
|View full text |Cite
|
Sign up to set email alerts
|

Salmonellain Wild Animals: A Public Health Concern

Abstract: Wildlife can be a reservoir of infectious agents for humans and domestic and wild animals. In this regard, widespread Salmonella spp. in wildlife is a problem for public and environmental health. Currently, more than 2500 serovars of Salmonella spp. are widely distributed among humans, animals, and the environment. This ubiquity favors the bidirectional transmission of the pathogen between wild and domestic animals. Moreover, when farmed animals acquire Salmonella spp. from wildlife, the likelihood of humans b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…These results reinforce the fact that the prevalence of Salmonella spp. is usually lower in wild than in domesticated animals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results reinforce the fact that the prevalence of Salmonella spp. is usually lower in wild than in domesticated animals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…in wild animals is lower than on the farm, despite the fact that wild animals can be asymptomatic carriers of Salmonella spp., with the bacterium remaining in equilibrium with the intestinal microbiota (dos Santos et al, 2022). A study carried out on 518 free-living wild animals including mammals, birds, and reptiles in forest fragments in Brazil from 2015 to 2021 showed that only three mammals and one bird were tested positive for Salmonella spp (dos Santos et al, 2022). Further investigations would be needed to calculate the frequency of likely contamination of S. Mbandaka from wild birds to farm animals in France.…”
Section: Figurementioning
confidence: 99%
“…The absence of a rigorous national agenda for monitoring salmonellae, the prevalence of human and animal carrier states, and the size and diversity of the animal reservoir make salmonellosis a serious problem for public health. [55]. Typhoid fever frequency is typically ranked from lowest (less than 10 cases per 100,000 people per year) to highest (greater than or equal to 500 cases per 100,000 people per year).…”
Section: Epidemiology Of Enteric Fevermentioning
confidence: 99%